Effect of different levels of macro nutrients (NPK) and mulching on growth, quality and yield of chrysanthemum (Dendranthema grandiflora) cv. Marigold - S, CHAITRA G; K, SEETHARAMU G; KUMAR, RAJIV; M, MUNIKRISHNAPPA P; M, SHIVANNA (The Indian Journal of Agricultural Sciences, 2018)
The present investigation was conducted to study the effect of different levels of nutrients (NPK) and mulching on various growth and flowering traits of chrysanthemum (Dendranthema grandiflora Tzvelev) cv. Marigold. The field experiment was laid out in randomized block design with five treatments and four replications during 2015- 16. The treatment consisted of different levels of nutrients and mulching, viz. 75% recommended dose of fertilizer (RDF) with mulching, 100% RDF with mulching, 125% RDF with mulching, 150% RDF with mulching and 100% RDF without mulching (control) and RDF was 120:150:100 kg NPK per ha. Results revealed that application of 150% RDF with mulching resulted in increased plant height (51.78 cm), leaf area (88.62 cm2), plant spread (N-S, 55.07 cm and E-W, 52.39 cm), number of laterals/plant (22.83) and number of suckers (11.17) after 120 days after planting (DAP). The same treatment has influenced early bud initiation (73.05 days), 50% flowering (103.60 days), increased flower diameter (5.44 cm), number of sprays per plant (14.40), highest flower yield per plant (658.35 g), and yield per ha (24.38 t), however, increased shelf life (6.55 days) was recorded from 125% RDF with mulching after 120 days after planting.